Design and Implementation of PWM-Based Speed Control and Monitoring System for Bucket Elevators in Wheat Flour Production - Rahma Nurdi; Yulkifli; Mona Berlian Sari (Research on Instrumentation, 2025)
In industrial wheat flour production, efficient material handling is essential to maintain product quality and streamline operations. One critical aspect is the transport of flour to storage silos using bucket elevators, where speed control plays a vital role in preventing delays and mechanical issues. This study presents the design and development of a prototype system for controlling and monitoring the speed of a bucket elevator using Pulse Width Modulation (PWM) technology. The system is built using an Arduino Uno microcontroller, LM393 speed sensor, INA219 voltage and current sensor, and a 12V DC motor with a PWM-based control interface. The proposed solution allows real-time adjustment of motor speed and accurate feedback through an integrated LCD and oscilloscope display. Experimental results show that the system achieves an average accuracy of 98.99% and a low error rate of 1.01% in both loaded and unloaded conditions. The findings confirm that PWM offers a reliable, efficient, and cost-effective method for speed regulation in vertical conveyor systems, particularly for sensitive materials such as wheat flour. This prototype serves as a scalable model for broader industrial applications in food processing.